Socio-economic Dimensions of Forest Honey (Bees dorsata) Business Development in Hiay Wetar Village, Southwest Maluku - Sahureka, Mersiana; ., Supratman; KS, Muhammad Alif; Suharti, Sri (KnE Social Sciences, 2024)
This research aims to 1) Understand the socio-economic characteristics of the community in developing the forest honey business - Apis dorsata bees. 2) Analyze the level of income from the forest honey business - Apis dorsata bees by the community in Hiay-Wetar village, Southwest Maluku. The research was conducted in Hiay Wetar village, Southwest Maluku in January-February 2024 using a purposive sampling method with 25 families as respondents. Primary and secondary data were taken through direct observation and interviews with respondents. The data obtained were analyzed using a quantitative and descriptive qualitative approach. The research results show that the social characteristics of the community greatly influence the respondents' activities in collecting/harvesting forest honey, namely age, education level, experience in collecting forest honey, number of family dependents, and income. Collecting honey bee hives starts with marking the tree, harvesting and packaging the honey is still done using simple production equipment and traditional techniques based on local knowledge and wisdom from generation to generation. The collection of forest honey by the people of Hiay Wetar village is called "cut wani "which means cut honey" and air wani which means honey bee water. In a year there are two honey harvests (cut wani), namely in April – June and October – December with a total production of 1500 liters per year and total sales of IDR 180,000,000/year. Net income of IDR 169,915,000.00 and R/C return ratio analysis of the honey business has a decent ratio with flat R/C = IDR 18.03. Keywords: economy, Apis dorsata bees, income, social, forest honey